"Synthesis of Co1−xGdxFe2O4+δ (0 ≥ x ≤ 0.1) and study of their magnetic, electric, and magneto-optical properties". Issue 16 (November 2017) - Montemayor, Sagrario M.; Mallada, C.; Vázquez, Noé; Menéndez, J.L.; Díaz-Guillén, J.A.; Rodríguez-Fernández, O.S.; Betancourt-Galindo, R.
Abstract: In this investigation, pure and gadolinium-doped cobalt ferrites (Co1−x Gdx Fe2 O4+δ, x= 0, 0.02, 0.04, 0.06, 0.08 y 0.1), were synthesized through a modified route of the coprecipitation method. X-ray diffraction technique shows a cubic phase of the spinel-type structure typically associated with these compounds. According to Scherrer's equation, the crystallite size can be tuned through the Gd 3+ content (26 nm to x= 0 and 9 nm to x= 0.1) or through the temperature of the thermal treatment (21 nm to 400 °C and 28 nm to 700 °C). The obtained powders show a ferrimagnetic behavior, at room temperature, with magnetization (reached at the maximum applied field) and coercivity values showing a dependence on the substitution grade of cobalt (II) by gadolinium (III) ions. At x= 0.02 the magnetization shows an increase of 7% (even when the particle size decreases a 40%) and the coercivity shows a decrease of 45%. DC conductivity of sintered ferrites is enhanced up to 3 orders of magnitude in the x= 0.1 substituted materials; while, keeping a constant transverse magneto-optical Kerr effect around 0.35%.